Investigation of relationship marketing in the franchising activity of trade companies - Lisun, Yanina (Technology audit and production reserves, 2017)
The article reveals the essence and constituents of the concepts of «relationship», «interaction», «marketing relations», «marketing partnership», «partnership» of the trade business. The essence of the terms «distribution» and «franchising» is investigated and the place of franchising in the structure of organizational and legal forms of distribution systems is determined. It analyses the activity of trading companies and the franchising market of Ukraine is conducted. The article analyses main strengths and weaknesses of franchising activity are summarized with the use of SWOT analysis, which makes it possible to clarify the nature of the partnership relations in the franchising business. The article shows that relationship marketing is a mechanism for the development of business entities based on the integration of basic functions, partnerships and corporate interests. Franchising framework consists of various forms and principles of cooperation, ranging from the simplest, which consists in the distribution of franchisor goods using its brand and trade standards, to the most complex form of cooperation, which consists in proposing an entire franchise system. It analyses the segmentation of franchises in the field of trade on the basis of such features as investments, the cost of a franchise, the payback period, the number of staff, technological requirements for doing business, which makes it possible to clarify the degree of manifestation (saturation) of the partnership.